Organizational aspects of neurorehabilitation at the outpatient stage - D. Khramtsov (Journal of Education, Health and Sport, 2021)
The study was aimed to evaluate the effectiveness of IRP implementation in patients of a specialized clinic providing long-term care to neurological and neurosurgical patients.